2021
DOI: 10.3390/healthcare9101384
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Awareness about Developmental Dysplasia of the Hip in Children among Pregnant Ladies in the Aseer Region, Southwestern Saudi Arabia

Abstract: Background: Developmental dysplasia of the hip (DDH) is classified as a group of malformations, varying from abnormal acetabulum (dysplasia) and mild subluxation of the femoral head to fixed displacement (congenital dislocation). This study aimed to assess the knowledge level and its determinants regarding DDH in children among pregnant females in the Aseer region of southwestern Saudi Arabia. Methods: A descriptive cross-sectional study was conducted targeting all pregnant females in the Aseer region between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
3
4
1
Order By: Relevance
“…The majority had a low knowledge level regarding DDH (72.8%), and only 5.1% had a high knowledge level, which is concerning considering surgical treatment of neglected DDH cases represents 30% of the surgical practice of pediatric orthopedic surgeons in the country [10]. In our study, females had a significantly higher knowledge score than males (p = 0.026), similar to a local study done among pregnant ladies that showed one-third of the participants had good awareness [13]. Education level was also significantly associated with knowledge score toward DDH (p = 0.01); it was observed that the higher the education level, the higher the knowledge score.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The majority had a low knowledge level regarding DDH (72.8%), and only 5.1% had a high knowledge level, which is concerning considering surgical treatment of neglected DDH cases represents 30% of the surgical practice of pediatric orthopedic surgeons in the country [10]. In our study, females had a significantly higher knowledge score than males (p = 0.026), similar to a local study done among pregnant ladies that showed one-third of the participants had good awareness [13]. Education level was also significantly associated with knowledge score toward DDH (p = 0.01); it was observed that the higher the education level, the higher the knowledge score.…”
Section: Discussionsupporting
confidence: 82%
“…Also, parents who reported having a child screened for DDH had a significantly higher knowledge score than those who did not have a child screened for DDH (p < 0.001). Also, having a first-degree relative with DDH was significantly associated with a knowledge score toward DDH (p < 0.001), this is similar to a study where 71.4% of the females having a child diagnosed with DDH had good awareness levels [13]. Moreover, the main source of knowledge on DDH was from an affected family member [8].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A better level of knowledge was observed among multiparous females who had a child with DDH and those who obtained their information through study or work in the medical sector [7]. Some studies assessed the awareness regarding DDH in community categories other than females.…”
Section: Barlow Maneuvermentioning
confidence: 99%